2021
DOI: 10.1097/brs.0000000000004027
|View full text |Cite
|
Sign up to set email alerts
|

The Long-term Fate of Asymptomatic Proximal Junctional Kyphosis Following Long Instrumented Fusion in Elderly Patients with Sagittal Imbalance

Abstract: Study Design. Retrospective study.Objective. The aim of this study was to investigate the longterm fate of asymptomatic PJK focusing on the elderly patients with sagittal imbalance by comparing the patients with and without PJK. Summary of Background Data. Most of previous studies demonstrated that PJK does not negatively affect the clinical outcome compared to that of the patients without PJK. The question ''will the asymptomatic PJK remain asymptomatic even in long-term follow-up?'' has not been answered yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Park et al compared patients who experienced PJK with those who did not and found no differences between the two groups in SVA. 21 To examine the impact of UIV on postoperative evolution, patients were stratified into those with UT and LT proximal fusion levels. Prior work comparing upper and lower thoracic UIV gives no definitive answers with regard to optimal approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al compared patients who experienced PJK with those who did not and found no differences between the two groups in SVA. 21 To examine the impact of UIV on postoperative evolution, patients were stratified into those with UT and LT proximal fusion levels. Prior work comparing upper and lower thoracic UIV gives no definitive answers with regard to optimal approach.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon holds true even in the setting of proximal junctional kyphosis. Park et al compared patients who experienced PJK with those who did not and found no differences between the two groups in SVA 21 …”
Section: Discussionmentioning
confidence: 99%
“…All patients met at least 1 or more of the following radiographic criteria: (1) sagittal vertical axis (SVA) ≥50 mm; (2) pelvic incidence (PI)-lumbar lordosis (LL) >10°; and (3) pelvic tilt (PT) >25°. 18,20,21 To eliminate the distal fusion segment-related bias to the SRFD, we only included patients who had their sacrum fused. In 2011, we created the Specific Functional Disability Index (SFDI), a measure for assessing daily specific functional disabilities after long segmented fusion (Table 1).…”
Section: Study Populationmentioning
confidence: 99%
“…9,[13][14][15][16] When looking at the time trends of change in postoperative outcomes after long segmental fusion for ASD, it has been wellknown that radiographic parameters and clinical outcomes can change over time. [17][18][19] In a similar way, we supposed that SRFD may not be a static concept and could change over time after surgery. There are infrequent studies about the time-dependent change in SRFD after long segmental spinal fusion.…”
mentioning
confidence: 99%
“…Large series have demonstrated similar Scoliosis Research Society (SRS)-24 scores in patients with and without PJK 2,3. Furthermore, radiographic PJK does not herald a need for revision surgery: rates of revision for PJK are as low as one-tenth the incidence of the radiographic finding 4,5. To rectify this issue, investigators have proposed increasing the PJA threshold to 20° or using classification schemes that take into account factors other than the PJA 6–8.…”
mentioning
confidence: 99%